Bridging the gap between laboratory and applied research on response‐independent schedules. Issue 1 (28th November 2022) - Ingvarsson, Einar T.; Fernandez, Eduardo J.
Abstract : In 1948, Skinner described the behavior of pigeons under response‐independent schedules as "superstitious, " and proposed that the responses were reinforced by contiguous, adventitious food deliveries. Subsequently, response‐independent schedules have been of interest to both basic and applied researchers, first to understand the mechanisms involved, and later, as "noncontingent reinforcement" (NCR) to reduce undesirable behavior. However, the potential superstitious effects produced by these schedules have been challenged, with some researchers arguing that antecedent variables play a significant role. This paper examines the evidence for adventitious reinforcement from both laboratory and applied research, the results of which suggest that antecedent, nonoperant functions may be important in fully understanding the effects of NCR. We propose an applied‐basic research synthesis, in which attention to potential nonoperant functions could provide a more complete understanding of response‐independent schedules. We conclude with a summary of the applied implications of the nonoperant functions of NCR schedules.